THE MIXED INTEGER LINEAR PROGRAMMINGMODEL FOR THE IMPORT PLANNING INDEFINITIVE CUSTOMS REGIME - Cornejo Sánchez, Christian (2005)
The article deals in the application of the Mixed Integer Linear Programming (MILP) as a tool for the import planning in the context of a company dealing in the manufacturing and sale of steel components. A mathematical model is built to be adapted for the characteristics of the company import processes and whose objective is to decide which import plan having definitive customs regimen has the minimum total costs. The mathematical pattern is formulated in this first part.